Perlindungan Hukum bagi Korban Tindak Pidana Perdagangan Orang yang Dipekerjakan di Situs Judi Online di Luar Negeri - Martin Benyamin Chandra; Ahmad Jamaludin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Cases of human trafficking involving Indonesian citizens in the online gambling sector abroad have been increasing, highlighting the urgency of more effective legal protection. This study aims to evaluate gaps in Indonesia's legal system, particularly in the implementation of Law No. 21 of 2007 and the effectiveness of international cooperation in handling cross-border cases. The research employs a normative juridical approach by analyzing regulations, court rulings, and related policies to identify weaknesses in victim protection mechanisms. It also examines the role of law enforcement agencies and relevant institutions in the investigation and repatriation process of human trafficking victims. The findings reveal that legal protection for victims of human trafficking in the online gambling sector under Law No. 21/2007 faces challenges related to jurisdiction, legal system differences, and corruption. The implementation of international cooperation remains suboptimal, leading to ineffective victim protection. Therefore, regulatory revisions, strengthened repatriation and rehabilitation mechanisms, and an anti-corruption oversight system are needed to ensure justice for victims.